Ahdāf al-Hindūsiyyah fī al-Khalīj al-'Arabī wa al-'Ālam al-Islāmī: Dirāsah Tārīkhiyyah Taḥlīliyyah Naqdiyyah 'Aqdiyyah - M Alhawsawi, Akram Mahmoud (Study Program of Arabic Language Teaching, 2026)
This study aims to examine the objectives of the Hindu presence in the Arab Gulf and the broader Islamic world from a historical, analytical, and doctrinally critical perspective. Specifically, it investigates the historical roots of this presence, analyzes the political, economic, and cultural factors that have contributed to its expansion, explores the doctrinal foundations of Hinduism and their implications for Islamic societies, and evaluates their impact on religious identity and value systems. The research employs a qualitative approach using historical and analytical methods supported by doctrinal criticism based on the Islamic theological framework. Data were collected through documentary research from books, scholarly articles, historical records, and relevant academic sources, and were analyzed using qualitative content analysis. The findings indicate that the contemporary Hindu presence in the Arab Gulf and the Islamic world has evolved beyond its traditional socio-economic function into a broader cultural and religious phenomenon. Rather than relying on direct proselytization, its influence is increasingly manifested through cultural representation, spiritual practices, economic networks, and soft power, thereby contributing to the gradual normalization of Hindu symbols and values within public spaces. The study further reveals that several philosophical concepts associated with Hinduism, when detached from their original religious context and presented as universal cultural or wellness practices, may generate doctrinal challenges for Muslim societies by affecting perceptions of monotheism, religious exclusivity, and Islamic identity. The study concludes that maintaining a balanced approach between peaceful coexistence and doctrinal integrity requires strengthening critical theological awareness, enhancing religious literacy, and developing scholarly approaches capable of addressing contemporary cross-cultural and interreligious interactions while preserving the religious and cultural identity of Muslim communities.